Mediação pedagógica: um estudo de caso sobre formação continuada e intervenção docente no contexto de uma escola pública - Mendes, Agatha Fernandes da Cunha (Universidade Federal de São Carlos, 2016)
This study aimed to investigate how is the mediation in teaching do about the teaching and learning of written language, and demonstrate how this work may have been impacted by the areas of continuing education. Therefore, we take as the object of analysis the work of a teacher with a class of 3rd year of elementary school in a public school in the state of São Paulo. The study also aimed to understand the meanings attributed by the teacher about the pedagogical proposal of the school and its influences to the teaching practice; the structuring of the pedagogical work in the pedagogical mediation in textual production activities and the perceptions of the teacher on the practices, activities and studies that are configured as a possibility for development for students in relation to textual production, and the teacher in relation to their teaching practice. The research was configured as a case study, using as methodological procedures participant observation and an interview with the participating teacher of this investigation. Descriptions and analyzes of the data produced during this process have been made taking as the theoretical foundations of the Theory Historical-Cultural. The results showed that the proposed studies and training undertaken at school was perceived as important for the teacher and influenced changes in their teaching practices, educational activities related to text production were organized systematically with mediation as an essential aspect in the activities proposals. This has contributed to advances in students' learning processes and influencing the teaching own relationship with knowledge. It discusses the important role of mediation and systematic and intentional interventions by the teacher as well as capabilities that arise from organized labor and grounded in theoretical foundations that depict the worldviews and subject to be formed.
Keywords: Professores - Formação; Teachers In-service training; Prática de ensino; Student teaching; Mediação pedagógica; Teoria histórico-cultural; Produção de texto; Pedagogical mediation; Historical and cultural theory; Text production; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM